Development of PCR primer systems for amplification of 16S-rDNA to detect of Thiobacillus spp - Beheshti Ale Agha, Ali; Kahrizi, Danial; Ahmadvand, Asma; Bashiri, Hoda; Fakhri, Roza (Cellular and Molecular Biology, 2017)
Thiobacillus is a genus of Gram-negative, rod-shaped and autotrophic Betaproteobacteria. They catalyze the dissimilatory oxidation of elemental sulfur and reduced inorganic sulfur compounds. Whereas more than 30 species have been known in this genus, most were never reliably or effectively published. The rest were either reclassified into Thiomonas, Paracoccus, Starkeya, Sulfuriferula, Halothiobacillus, Thermithiobacillus or Acidithiobacillus, were lost from culture. Most of Thiobacillus species are obligate autotrophs via elementary sulfur, thiosulfate or polythionates as energy sources. Based on 16S ribosomal RNA sequence analysis, many members of Thiobacillus have been reclassified. A system was developed for the detection of Thiobacillus bacteria by the amplification of specific 16S ribosomal RNA sequence gene (16S rDNA) fragments with PCR. Primer sequences were designed for the amplification of fragments of 16S rDNA.